Low Frequency Atmospheric Noise Studies and Long Wave Technology Interfaces - Warber, Chris R. (1998)
The results of the work done under contract DNA 001-93-C-0146 are discussed. This work included changes and improvement to the long wave noise propagation code LNP, development of a new ground conductivity model for use in LNP and as a separate code. In addition, under this contract we demonstrated that LNP could be used in a system to forecast noise levels in a manner similar to weather forecasts. The techniques developed to do this are discussed.